The problem of the incidence of falls in hospitals in Poland in the opinion of physiotherapists - Mikos, Marcin; Ciukszo, Agnieszka; Podhorecka, Marta; Curyło, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction: An unintentional fall is an event whereby a person inadvertently comes to rest on the ground or floor for reasons other than a violent impact, loss of consciousness, or the sudden onset of paralysis that can occur during a stroke or epileptic seizure. Implementing effective strategies can reduce the risk of falls, reduce fall-related injuries and reduce healthcare costs. Aim: The aim of the study was to get to know the opinion of physiotherapists working in one of the Krakow multi-specialty hospitals on the risk of falls in hospitals in Poland. Material and methods: Thirty physiotherapists participated in the study. The study was conducted using a proprietary questionnaire consisting of 44 questions. Results: The most common place in the hospital where, according to the respondents, a fall occurs is the toilet, bathroom, corridor and patient room. 80% of respondents indicate that physiotherapists in Poland are sufficiently prepared to conduct professional activities aimed at preventing patients from falling in hospitals. Conclusions: Falls of patients in hospitals in Poland are a significant systemic problem. The main causes of patient falls in the hospital were indicated by the respondents as staff shortage, poor technical condition of infrastructure and underfunding of health care. According to the surveyed physiotherapists, most falls are recorded in the departments of rehabilitation and internal medicine, which is confirmed by the cited literature.